Investigation of acute and sub-chronic oral toxicity and effects of Allium ascalonicum L. extract on Triton WR1339-induced hyperlipidemia on Swiss albino mice - Duyen Thi My Huynh; Tran Huynh; Minh-Ngoc T. Le; Huynh Nhu Mai (Elsevier, 2024)
Introduction: Metabolic disorders are increasingly rapidly becoming a burden on global healthcare systems. Among these, hyperlipidemia frequently leads to cardiovascular diseases such as myocardial infarction and cerebral stroke, posing significant life-threatening risks. The pharmacological drugs, which are often costly and may cause a range of adverse side effects detrimental to health. Allium ascalonicum L., a member of the Alliaceae family, a widely used species of the Allium genus, is commonly employed as a spice and food ingredient in Asia. Allium ascalonicum (AS) is rich in triterpenoids, phenolic acids, flavonoids, thiosulfates, and anthocyanins, whose therapeutic effects have been documented. In Chinese, Allium ascalonicum L. is known as 葱 (Cōng), which is used for various types of onions and similar plants in Chinese, including shallots. Ancient Chinese medicine documented that AS has a sweet and mildly spicy taste with a slight astringency and is warm in nature. In traditional Chinese medicine, AS is prepared as infusions, juices, and poultices to harness their health benefits, and commonly used in cooking for their nutritional and medicinal purposes. Modern medicine has discovered that this type of bulb possesses antibacterial and anti-inflammatory properties, acts as a diuretic, treats diarrhea, reduces blood sugar levels, lowers blood pressure, reduces cholesterol, and among its other roles. Currently, there is a lack of in vivo study on the cholesterol-regulating potential of AS. Methods: For our experiments, 24 and 32 Swiss albino mice were employed to investigate the acute and sub-chronic oral toxicity according to the Guidelines for preclinical and clinical trials of Traditional Medicine and Herbal Medicines by the Vietnam Ministry of Health and OECD. To investigate the effects on hyperlipidemia, 40 mice of both sexes were divided into five groups (n = 6-8 each). Tyloxapol (Triton WR1339, 400 mg/kg, i.p.) was used to induce hyperlipidemia. Atorvastatin (60 mg/kg, p.o.) was used as the standard, and AS extract was conducted at the doses of 500 mg/kg and 1000 mg/kg. Hyperlipidemic activity was assessed using a variety of parameters. Results: Allium ascalonicum (AS) extract showed no acute toxicity and sub-chronic toxicity. The AS showed a significant decrease in total cholesterol, triglycerides and LDL-c but showed no changes in HDL-c. Conclusion: Our results indicated that AS is safe to use for a longtime and has a potential as an antihyperlipidemic agent, possibly due to its ability to inhibit the elevation of total cholesterol, triglycerides and LDL-c. The AS is rich in phytochemicals like triterpenoids, flavonoids and saponins, which may contribute to its hypolipidemic effect.